Post-Emancipation Indenture and Migration : Identities, Racialization and Transnationalism - Bastos, Cristiana,; Hassankhan, Maurits S.,; Hiralal, Kalpana,; Roopnarine, Lomarsh, (Brill | Manohar Publishers & Distributors, 2023)
The chapters in this volume contribute to the current scholarship on historical and contemporary migrations by providing new interdisciplinary approaches to historical and contemporary global migratory issues, while simultaneously analyzing ethnicization, identity formation, racialization, citizenship, nationalism, and Tansnationalism. Themes such as border crossing, forced migration, displacement, and statelessness are problematized, and in the process, challenge existing dominant metanarratives. One distinctive feature is how marginalized and silenced voices shift from the margin to the centre of migration narratives, reinforced by the fact that most contributors write from an insider's perspective.